2009
DOI: 10.1108/00907320910935002
|View full text |Cite
|
Sign up to set email alerts
|

Full‐text articles: faculty perceptions, student use, and citation abuse

Abstract: Purpose -The purpose of this paper is to seek to explore faculty perceptions versus actual student usage of print and online, full-text articles. Design/methodology/approach -Surveys were given to faculty and their students at four Penn State campuses. Both the six-question instructor survey and the 11-question student survey related to article retrieval for one particular class assignment. Findings -Data gathered from the surveys surprisingly indicated that faculty are overestimating student use of online art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Students see Internet, and more specifically search engines and academic databases, as the starting point when it comes to searching for information (Dilek-Kayaoglu, 2014). However, they need further information about how to correctly cite and reference these sources (Imler & Hall, 2009). Our results prove this, as 40.1% of the students search for information in databases with high or very high frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Students see Internet, and more specifically search engines and academic databases, as the starting point when it comes to searching for information (Dilek-Kayaoglu, 2014). However, they need further information about how to correctly cite and reference these sources (Imler & Hall, 2009). Our results prove this, as 40.1% of the students search for information in databases with high or very high frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Hall from 2008 found that students used the library's print journals 21 per cent of the time and electronic journal articles 65 per cent of the time. The study also states that 70 per cent of students rejected an article, because it was not available in full text from the database they were using (Imler and Hall, 2009). A study of MBA students in Singapore found that 65 per cent of the students mainly used electronic sources, while 20 per cent used print and electronic sources equally, and only 15 per cent said that they mainly used print resources.…”
Section: Twenty-first-century Authorshipmentioning
confidence: 99%
“…On the other end of the spectrum, they found that 11% of students retrieved 25% of recently acquired articles from a full-text database and 75% using another means-these included interlibrary loan, actual library access and other means. In a 2009 study on fulltext article use, Imler & Hall asked students to qualify how they accessed the articles that they used for a paper and found that 65% came from full-text databases, 21% from print, and 13% from ILL (Imler & Hall, 2009).…”
Section: Tablementioning
confidence: 99%
“…At the mercy of convenience alone, returned search results that do not have the full-text immediately available are often dismissed by students. Imler & Hall (2009) found that 70% of students admitted to rejecting an article for their paper if the full-text was not immediately available on their computer. Full-text databases are even designed to cater to this type of user, if they are aware of it, and most come equipped with a simple filter that removes any search result that does not contain a full-text version of the article.…”
Section: Tablementioning
confidence: 99%